1985
DOI: 10.1139/v85-433
|View full text |Cite
|
Sign up to set email alerts
|

The gas phase reactions of the trichloromethylium ion with alkyl aromatics, studied by high pressure mass spectrometry

Abstract: The reactions of trichloromethylium (CCl3+) with benzene and the lower alkyl aromatics (ArH) have been studied by high pressure mass spectrometry at pressures in the range 2–4 Torr and temperatures from 300 to 560 K. The only two primary products are the adduct ArHCCl3+ and ArCCl2+, which is formed by loss of HCl from the adduct. The relative yields of adduct increase with increasing number of methyl substituents on the aromatic ring (benzene → mesitylene). The disappearance of CCl3+ is kinetically second orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In earlier experiments with CC13+ using high pressure mass spectrometry (HPMS) with ion source pressures in the range 2-5 Torr, we found that stable aromatic.CC13' adducts were observable (2) whereas previous studies at much lower ion source pressures (-Torr) had failed to detect such species (3,4). Thus while collisional stabilization is not of importance at low pressures, it can be of significance at the higher pressures of our HPMS studies.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In earlier experiments with CC13+ using high pressure mass spectrometry (HPMS) with ion source pressures in the range 2-5 Torr, we found that stable aromatic.CC13' adducts were observable (2) whereas previous studies at much lower ion source pressures (-Torr) had failed to detect such species (3,4). Thus while collisional stabilization is not of importance at low pressures, it can be of significance at the higher pressures of our HPMS studies.…”
mentioning
confidence: 63%
“…Results and discussion CC13+ is formed from CC14 by dissociative proton transfer from CH5+ and C2H5+, the major reagent ions in methane (2).…”
Section: Methodsmentioning
confidence: 99%